Experience of Using the ANZI Strain Cell for Three-Dimensional, In Situ Stress Determinations in Deep Exploration Boreholes - Ken Mills; Jesse Puller (International Conference on Ground Control in Mining, 2018)
"This paper describes the Australia, New Zealand Inflatable (ANZI) strain cell, its operation, and recent development for overcoring in exploration boreholes. The ANZI strain cell is an instrument system that uses the overcoring method of stress relief to determine the three-dimensional, in-situ stresses in rock. The instrument has been used successfully for over three decades in numerous underground mining and civil projects, but technical advances over the last decade or so have allowed the system to be deployed in surface exploration boreholes to greater depths than was previously possible. Recent development of a downhole electronic data logger, a wireline-enabled drilling system, and an instrument deployment system has simplified the process of obtaining three-dimensional overcore measurements at depths approaching 1km to a single shift operation.The capability to deploy ANZI strain cells in surface exploration boreholes represents a significant breakthrough for the design of underground mines and underground excavations generally. High-confidence characterisation of the in-situ stresses at the design stage provides the opportunity to design key infrastructure and mining systems to take advantage of the in-situ stress field from the outset before mining begins. Understanding the three-dimensional, in-situ stress field not only provides a measure of the magnitude and direction of loads acting within the rock mass, it also provides insight into the mechanics of all the various processes driving ground deformations, including which geological fault structures are at limiting equilibrium.INTRODUCTIONThe overcoring method of stress relief is one of the most direct methods for determining three-dimensional, in-situ stresses in rock. The Australia, New Zealand Inflatable (ANZI) strain cell combines overcoring with several other techniques to provide determinations of the three-dimensional, in-situ stress field and the properties of the rock and, importantly, provides an indication of how much confidence can be placed in the measurement. This paper describes the advances that have enabled overcoring of the ANZI strain cell in deep surface exploration boreholes and the development of various complementary techniques that build additional confidence in the determination of the in-situ stress."